Penerapan Model Kemandirian Keluarga Dalam Merawat Lansia Dengan Hipertensi Melalui Pendekatan Teori Orem (Self-Care) Di Desa Mongolato Kecamatan Telaga - Rona Febriyona; Juliana Mayulu (Pusat Riset dan Inovasi Nasional, 2023)
Hypertension is a degenerative or non-communicable disease that is still high in cases as a contributor to morbidity and death rates in the community and often occurs in the elderly. The main focus of the conceptual model of self-care is to improve the ability of a person or family to care for himself and his family members independently so as to achieve the ability to maintain their health and well-being, because according to Orem, self-care is not a process of intuition, but a behavior that can be learned through the process of learning. The type of research used in this study is experimental design (one group pre-test post-test design), the study was carried out by means before treatment / treatment, the dependent variable was observed and measured blood pressure first (pre-test), after that treatment / treatment was carried out using instruments in the form of SAP, after treatment was observed and measured again blood pressure (post-test). The population in this study was 3 families with elderly people with hypertension in Mongolato Village, Telaga District. The results of data analysis from the data review found nursing problems, namely Knowledge Deficit and Health Behavior tend to be risky. The implementation carried out by the researcher is counseling using liflets about hypertension and Self-Care Management based on Orem Theory. The overall evaluation, after nursing actions, was obtained, namely increasing knowledge from each family about hypertension and being able to independently the elderly suffering from hypertension through their families based on the theory of Orem Self-Care Management.